High sodium state P2 type layered oxide material for sodium ion battery positive electrode
By regulating the copper ion valence state and doping concentration range in the P2-type layered oxide material, the P2 phase with high sodium content is solved, and the problem of insufficient sodium content in the sodium ion battery positive electrode material is achieved, and a high-performance and safe sodium ion battery positive electrode material is achieved.
Patent Information
- Application Number
- CN202411792965.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-08
AI Technical Summary
Among the existing sodium ion battery positive electrode materials, the P2 layered oxide material is insufficient, resulting in the need for sodium supplementation in full battery applications, affecting safety and energy density.
By regulating the copper ion valence state and doping concentration range in the P2 layered oxide material, the P2 thermodynamic stable phase of the material at a specific temperature and time is locked, thereby achieving the generation of P2 phase with a high sodium content (0.98~1.4).
The high-sodium P2-type layered oxide material has high pure phase, good safety and excellent electrochemical performance, avoiding the cost and safety problems brought about by pre-sodiumization technology, and solving the problem of sodium deficiency in all battery applications.
Smart Images

Figure CN119742361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode high sodium state P2 type layered oxide material. Background Art
[0002] With the increasing consumption of fossil fuels, it is widely recognized that there is an urgent need to develop energy storage technologies with high energy efficiency and cost-effectiveness. In the past three decades, lithium-ion batteries have been widely used in various fields due to their high energy density among existing rechargeable batteries. However, the high cost and limited resources of lithium restrict its large-scale application. In this context, sodium-ion batteries (SIBs) are considered to be a viable energy storage system due to their low cost, widely distributed sodium resources and environmental friendliness. In particular, electrode materials have made rapid progress recently, such as carbon as anode materials and Prussian blue compounds, polyanion compounds, layered metal oxides and organic compound materials as cathode materials of SIBs. As a key part of SIBs, cathode materials play a key role in determining cost and performance. For sodium-ion batteries, how to achieve high performance with low cost is the top priority in the study of sodium-ion batteries. Among the cathode materials of sodium-ion batteries, layered oxide materials have become one of the main cathode materials of sodium-ion batteries because of their periodic layered structure, simple preparation method, high specific capacity and voltage.
[0003] The oxide cathode materials in sodium ion batteries are mainly divided into layered oxides and tunnel-structured oxides. The layered structure is the most widely studied due to its high energy density and easy preparation. The layered structure is usually composed of transition metal elements and the MO6 octahedral structure formed by the six surrounding oxygens to form a transition metal layer, and the sodium ions are between the transition metal layers, forming a structure in which MO6 and NaO6 are alternately arranged. Delmas et al. divided the layered oxides into O3, O2, P3 and P2 structures according to the coordination configuration of sodium ions in the MO6 polyhedron and the stacking mode of oxygen. The capital letters represent the coordination configuration of sodium ions; O is the abbreviation of Octahedral, P is the abbreviation of Prismatic, that is, the triangular prism position, and the number represents the stacking layer number of the minimum repeating unit of oxygen (2-ABBA, 3-ABCABC). In the O3 structure, the sodium ion has only one position, which is connected with the transition metal MO6 to form a NaO6 octahedron. In the P3 structure, there is only one NaO6 triangular prism position; while in the P2 structure, there are two positions, triangular prism and octahedron, which are the same as the edge and the same as the face. e and Na f .
[0004] In the application of layered oxide cathode materials, using cheap metal ions to construct cathode materials with long cycle life, high charge and discharge rate, and high discharge specific capacity has become one of the important research topics. x For MO2 (M=Fe, Co, Ni, Mn, Cu, Mg, Cr, Ca, Ba, Ti, V), it is usually difficult to have both high specific capacity and long cycle. In practice, due to the different ranges of sodium content x in the molecular formula, different configurations are formed. These configurations mainly include the above-mentioned P2, P3, O3, and O2 structures. For the O3 structure, its phase change is complex, with complex phase changes such as O3-P3-P3'-P3''-O1, and the structural stability during the charge and discharge cycle is often insufficient. The advantage of the P2 phase structure is that its phase change process is simpler and more reversible, which is P2-O2. During the charging process, the structural life is more stable, and the P2 phase has Na f / Na e Compared with the O3 phase, the two types of Na removal sites have more diffusion channels and better rate performance. As for the generation mechanism of Na content, when the sodium content in the oxide is low (x < 0.5), the oxide with a three-dimensional tunnel structure is dominant. The P2 phase is often generated in a sodium-deficient state (between 0.67 and 0.83), which is one of the thorny issues of the P2 phase. The sodium content of the O3 phase is generally around 1.
[0005] Chinese invention patent application CN116259742A discloses a copper-manganese-based sodium-ion battery positive electrode material and a preparation method thereof. Although a low-cost, long-cycle vacancy-disordered copper-manganese-based layered positive electrode material is constructed through an ion doping strategy, its sodium content can only be between 0.67 and 0.85, which is still in a serious sodium-deficient state. When used as a positive electrode in a full battery, sodium supplementation measures are still required for normal use, which limits its large-scale application.
[0006] Chinese invention patent application CN104617288A discloses a copper-based sodium-rich layered oxide material and its preparation method and use, which uses Cu to replace Ni and Co, and uses non-toxic elements that are abundant in the earth's crust to obtain a P2 phase layered positive electrode material. However, the Na ratio selected can only reach between 0.67 and 0.9, which is still in a sodium-poor state, and sodium supplementation measures are indispensable in actual full battery applications.
[0007] To solve the problem of insufficient sodium content in P2 materials, it is often necessary to combine pre-sodiumization technology, but it also faces certain problems and cost disadvantages. Through pre-sodiumization, a portion of sodium ions can be pre-stored in the sodium-ion battery to compensate for the lack of sodium in the full battery cycle.
[0008] Based on this, various pre-sodiumization methods including cathode and anode pre-sodiumization have been explored. Adding self-sacrificial additives to the cathode electrode is a direct and effective way to provide additional sodium source. However, the additives will inevitably decompose and produce gas and solid byproducts in subsequent cycles, which may affect the safety of the battery and have an adverse effect on the cycle. In addition, the introduction of excessive additives will significantly increase the mass of the battery, thereby reducing the energy density. Summary of the invention
[0009] The purpose of the present invention is to provide a sodium-ion battery positive electrode high-sodium state P2-type layered oxide material, which has the characteristics of high phase purity, good safety and excellent electrochemical performance.
[0010] The present invention can be implemented by the following technical solutions: The present invention discloses a sodium ion battery positive electrode high sodium state P2 type layered oxide material, the chemical general formula of the high sodium state P2 type layered oxide material is: Na x Mn 1-y Cu y O 2+δ ; Among them, Cu and Mn form octahedral structures with the six adjacent oxygen atoms respectively, and multiple octahedral structures are arranged with the same edge to form a transition metal layer; sodium ions are located between every two transition metal layers, forming a layered oxide of the P2 phase, and the space group is P63 / mmc; The relationship between x, y and z satisfies the charge balance: x+3(1-y)+2y=2(2+δ), where 0.98<x≤1.4, 0.18≤y≤0.35; -0.05≤δ≤0.05.
[0011] Within the protection range of each element parameter in the above structural formula, by limiting the doping concentration range of Cu(II), the layered oxide material Na x Mn 1-y Cu y O 2+δ P2 type thermodynamically stable phase at a specific temperature and time. Controlling the Cu(II) doping range of 0.18≤y≤0.35 will make Cu(II) present a superstructural distribution in the above structure, which is conducive to accommodating more Na around Cu(II). + To achieve charge balance, it is possible to generate P2 phase with high sodium content (0.98~1.4); while leaving this doping range, it is very easy to generate P3 and O3 phase oxides. This is because the change of doping ion content will bring about the change of ion potential, thus affecting the Na +The distribution in the bulk phase of the material, combined with the influence of ion thermodynamics in the precursor under temperature and holding time, makes sodium ions with high sodium content under specific conditions tend to generate P2 phase as the final stable phase rather than O3 phase.
[0012] In the present invention, for P2 phase materials, in the high sodium state feed ratio, by controlling the specific copper ion valence state and doping concentration range, its thermodynamically stable phase at a specific temperature and time can be regulated, which makes it possible to generate a P2 phase with a high sodium content (0.98~1.4), while leaving this condition often generates oxides composed of P3 and O3 phases. This depends on the change in the ionic potential of the doped ions, which affects the distribution of Na ions in the bulk phase of the material, and the ion thermodynamics in the precursor under different temperature holding times make the sodium ions tend to generate P2 phase as the final stable phase. At the same time, we combine the precursor freeze-drying technology (to ensure uniform ion dispersion in the precursor) to make the ions uniformly transported during the sintering process, which promotes the generation of pure P2 phase in the sodium-rich state. The high sodium state has a higher sodium content than ordinary P2-type oxide materials. Compared with the above-mentioned pre-sodiumization technology, the high sodium state P2-type oxide material of the present invention is equivalent to playing the role of self-sodium replenishing material, which not only reduces the pre-sodium cost, but also solves the gas production, safety and other problems brought by the pre-sodiumization technology. At the same time, it also solves the application problem of the whole battery, and the material can be produced on a large scale.
[0013] Furthermore, the high sodium state P2 type layered oxide material is prepared by a sol-gel method or a solid phase method.
[0014] Furthermore, the preparation process of the sol-gel method comprises the following steps: S1. Preparation of precursor solution: Sodium nitrate, manganese nitrate and copper nitrate are weighed according to a molar ratio of sodium element to manganese element of 0.98-1.512, and dissolved in deionized water, and stirred to obtain a uniform precursor solution; S2. Preparation of citric acid solution: weigh citric acid monohydrate, stir to completely dissolve it to obtain a citric acid solution with a mass percentage concentration range of 10% to 30%; S3, preparation of precursor dry gel: adding the precursor solution in step S1 to the citric acid solution in step S2, and then continuously stirring at a controlled temperature of 40-60° C. to form a uniform wet gel, and drying the wet gel to obtain a precursor dry gel; S4, high temperature calcination: pre-calcine the precursor dry gel described in step S3 in an air atmosphere at 450-550°C for 4-8h, crush and mix again, calcine in an air atmosphere at 750-900°C for 8-15h, and obtain a high sodium state P2 type layered oxide positive electrode material after natural cooling.
[0015] Furthermore, in the sol-gel method, the molar ratio of metal ions to monohydrated citric acid in the precursor solution is 0.5 to 1. Compared with uneven cooling or rapid cooling, natural cooling often generates a thermodynamically stable phase of the material, and can promote uniform growth of the material, and the generated material has good crystallinity.
[0016] Furthermore, in step S3, the drying method is freeze drying and / or spray drying.
[0017] Furthermore, the preparation process of the solid phase method comprises the following steps: A1. Preparation of precursor powder: Sodium carbonate, manganese source and copper oxide are weighed according to a stoichiometric ratio and mixed to obtain a precursor powder; A2, high temperature calcination: The precursor powder described in A1 is calcined at 750 ~ 900 ° C in air atmosphere for 8 ~ 15 hours, and the high sodium state P2 type layered oxide positive electrode material is obtained after natural cooling. Compared with uneven cooling or rapid cooling, natural cooling often generates a thermodynamically stable phase of the material, and can promote uniform growth of the material, and the generated material has good crystallinity.
[0018] Furthermore, in step A1, the molar ratio of sodium element to transition metal element is 0.98-1.512.
[0019] Furthermore, in step A1, the manganese source is one or more of manganese trioxide, manganese dioxide, and manganese carbonate.
[0020] Further, in step A1, the mixing method is ball milling and / or stirring.
[0021] The present invention discloses a sodium ion battery positive electrode high sodium state P2 type layered oxide material, which has the following beneficial effects: A new type of P2-type structure material with high sodium state was synthesized by using cheap elements of manganese and copper in the transition metal layer. x Mn 1-y Cu y O 2+δ , x+3(1-y)+2y=2(2+δ), where 0.98<x≤1.4; 0.18≤y≤0.35; -0.05≤δ≤0.05. Within the protection range of each element parameter in the structural formula, by limiting the doping concentration range of Cu(II), the layered oxide material Na can be locked. x Mn 1-y Cu y O 2+δ P2 type thermodynamically stable phase at a specific temperature and time. Controlling the Cu(II) doping range of 0.18≤y≤0.35 will make Cu(II) present a superstructural distribution in the above structure, which is conducive to accommodating more Na around Cu(II).+ To achieve charge balance, it is possible to generate P2 phase with high sodium content (0.98~1.4); while leaving this doping range, it is very easy to generate P3 and O3 phase oxides. This is because the change of doping ion content will bring about the change of ion potential, thus affecting the Na + The distribution in the bulk phase of the material, combined with the influence of ion thermodynamics in the precursor under temperature and holding time, makes sodium ions with high sodium content under specific conditions tend to generate P2 phase as the final stable phase rather than O3 phase.
[0022] Combined with the precursor freeze drying technology, freeze drying is also called sublimation drying, which is a drying method that freezes the water-containing material below the freezing point, converts the water into ice, and then converts the ice into steam under a higher vacuum to remove it. The material can be frozen in a freezing device first, and then dried. Freeze drying can reduce the phenomenon of uneven ion transmission caused by heating of the precursor, ensure uniform dispersion of ions in the precursor, and make the ions evenly transmitted during the sintering process, which promotes the formation of pure P2 phase.
[0023] The high sodium state has a higher sodium content than ordinary P2-type layered oxide materials. Compared with the traditional pre-sodiumization technology, the high sodium state P2-type layered oxide material of the present invention is equivalent to self-supplementing sodium, which not only eliminates the need for the additional addition of pre-sodiumization reagents, equipment or process costs, but also solves the gas production, safety and other problems caused by the pre-sodiumization technology. At the same time, it also solves the application bottleneck of P2-type layered oxides in full batteries, which will promote the large-scale production and application of P2-type layered oxide materials. . BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The X-ray diffraction patterns of high sodium layered oxide materials with different sodium contents; Figure 2 The optimum ratio of P2 - Na in Example 2 is x Mn 1-y Cu y O 2+δ 300-cycle 1C long cycle diagram of a series of layered oxide materials; Figure 3 This is a comparison chart of 300 1C long cycles of different oxide materials generated under the conditions of Example 4 and Comparative Example 1. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0026] The present invention discloses a sodium ion battery positive electrode high sodium state P2 type layered oxide material, the chemical general formula of the high sodium state P2 type layered oxide material is: Na xMn 1-y Cu y O 2+δ ; Among them, Cu and Mn form octahedral structures with the six adjacent oxygen atoms respectively, and multiple octahedral structures are arranged with the same edge to form a transition metal layer; sodium ions are located between every two transition metal layers, forming a layered oxide of the P2 phase, and the space group is P63 / mmc; The relationship between x, y and z satisfies the charge balance: x+3(1-y)+2y=2(2+δ), where 0.98<x≤1.4, 0.18≤y≤0.35; -0.05≤δ≤0.05.
[0027] Furthermore, the high sodium state P2 type layered oxide material is prepared by a sol-gel method or a solid phase method.
[0028] Furthermore, the preparation process of the sol-gel method comprises the following steps: S1. Preparation of precursor solution: Sodium nitrate, manganese nitrate and copper nitrate are weighed according to a molar ratio of sodium element to manganese element of 0.98-1.512, and dissolved in deionized water, and stirred to obtain a uniform precursor solution; S2. Preparation of citric acid solution: weigh citric acid monohydrate, stir to completely dissolve it to obtain a citric acid solution with a mass percentage concentration range of 10% to 30%; S3, preparation of precursor dry gel: adding the precursor solution in step S1 to the citric acid solution in step S2, and then continuously stirring at a controlled temperature of 40-60° C. to form a uniform wet gel, and drying the wet gel to obtain a precursor dry gel; S4, high temperature calcination: pre-calcine the precursor dry gel described in step S3 in an air atmosphere at 450-550°C for 4-8h, crush and mix again, calcine in an air atmosphere at 750-900°C for 8-15h, and obtain a high sodium state P2 type layered oxide positive electrode material after natural cooling.
[0029] Furthermore, in the sol-gel method, the molar ratio of the metal ions to the monohydrated citric acid in the precursor solution is 0.5-1.
[0030] Furthermore, in step S3, the drying method is freeze drying and / or spray drying.
[0031] Furthermore, the preparation process of the solid phase method comprises the following steps: A1. Preparation of precursor powder: Sodium carbonate, manganese source and copper oxide are weighed according to a stoichiometric ratio and mixed to obtain a precursor powder; A2. High-temperature calcination: calcine the precursor powder described in A1 at 750-900 °C in an air atmosphere for 8-15 hours, and then cool naturally to obtain a high-sodium P2-type layered oxide positive electrode material.
[0032] Furthermore, in step A1, the molar ratio of sodium element to transition metal element is 0.98-1.512.
[0033] Furthermore, in step A1, the manganese source is one or more of manganese trioxide, manganese dioxide, and manganese carbonate.
[0034] Example 1 This embodiment provides a method for preparing high sodium state P2 type layered oxide, specifically a solid phase method. The process flow is as follows: Step S1, preparing Na by high temperature solid phase reaction 1.00 Mn 0.8 Cu 0.2 O2 material: Weigh 0.021 mmol of sodium carbonate, 0.02 mmol of manganese carbonate and copper oxide, and mix them to obtain a precursor powder, wherein the molar ratio of sodium element to transition metal element (the sum of manganese and copper) is 1.05:1.00. Step S2: transfer all the weighed sample powders into a 100 ml agate ball mill at once, add 10 ml of ethanol or acetone as a powder dispersant, and mix the sample powders into a paste.
[0035] Step S3, placing the 100 ml agate ball mill jar of step S2 into a QM-3C ball mill, the ball milling time is 12 h, and the ball milling speed is 400 rpm.
[0036] Step S4, after the ball milling is completed, the paste-like material obtained in step S3 is dried, ground, and pressed into thin sheets using a tablet press and a tablet press at a pressure of 15 MPa.
[0037] Step S5, then, the pressed disc is placed in a crucible, and placed in a muffle furnace at a calcination temperature of 800 °C. The sample is calcined in an air atmosphere for 12 h, and the muffle furnace heating rate is 3 °C min -1 .
[0038] Step S6, after the sample in step S5 is naturally cooled to room temperature, the sample is taken out and ground again, and the ground final product is transferred to an anhydrous and oxygen-free glove box for storage. The final black powder obtained is Na 1.00 Mn 0.8 Cu 0.2 O2 material.
[0039] This embodiment provides a method for preparing a high-sodium layered oxide material, which can be used to prepare the high-sodium layered oxide material described in the above embodiment 1. The method provided in this embodiment is simple, easy to implement, low-cost, and suitable for large-scale manufacturing applications.
[0040] Example 2 This embodiment provides a method for preparing a high sodium state P2-type layered oxide, specifically a sol-gel method, comprising: Step S1, preparing Na by sol-gel method 1.00 Mn 0.8 Cu 0.2 O2 material.
[0041] Step S2, the specific process is as follows: weigh 0.021 mmol of sodium nitrate, 0.02 mmol of 50 wt% manganese nitrate tetrahydrate, and copper nitrate trihydrate in proportion, and dissolve them in 50 ml of deionized water, wherein the molar ratio of sodium element to transition metal element (the sum of manganese and copper) is 1.05:1.00. Heat and stir at 40 degrees to obtain a uniform precursor solution.
[0042] Step S3, weigh 0.04 mmol, 8.4048 g of citric acid monohydrate, transfer it into 25 ml of deionized water, stir it thoroughly to completely dissolve it into a transparent colorless citric acid solution. The mass percentage concentration range of the citric acid solution is 26%.
[0043] Step S4, select a pipette and add the solution of step S2 dropwise into the citric acid solution of step S3, and then continue stirring at 80° C. until a uniform wet gel is formed.
[0044] Step S5, placing the wet gel obtained in step S4 in a freeze dryer for freeze drying to obtain a precursor dry gel.
[0045] Step S6, placing the dry gel obtained in step S5 in a mortar and grinding it evenly to obtain a fine powder.
[0046] Step S7, placing the powder from step S6 in a crucible and pre-calcining it in a muffle furnace at 450 °C for 6 h.
[0047] Step S8, pressing the pre-sintered product obtained in step S7 into thin sheets using a tablet press and a tablet press at a pressure of 15 MPa.
[0048] Step S9, placing the tablet product obtained in step S8 in a corundum porcelain boat, calcining at 800 ° C for 12 h in an air atmosphere in a muffle furnace, and cooling naturally. Step S10, after the sample in step S9 is naturally cooled to room temperature, the sample is taken out and re-ground, and the ground final product is transferred to an anhydrous and oxygen-free glove box for storage. The final black powder obtained is Na 1.00 Mn 0.8 Cu 0.2 O2 material.
[0049] This embodiment provides a method for preparing a high-sodium layered oxide material, which can be used to prepare the high-sodium layered oxide material described in the above embodiment 12. The method provided in this embodiment is simple, easy to implement, low-cost, and suitable for large-scale manufacturing applications.
[0050] Example 3 This embodiment provides a method for preparing a high-sodium P2-type layered oxide, specifically a spray-drying method.
[0051] Step S1, preparing Na by spray-drying method (sol-gel) 1.1 Mn 0.8 Cu 0.2 O2 material.
[0052] Step S2, the specific process is as follows: weigh 0.0231 mmol of sodium nitrate, 0.02 mmol of 50 wt% manganese nitrate tetrahydrate, and copper nitrate trihydrate in proportion, and dissolve them in 50 ml of deionized water, wherein the molar ratio of sodium element to transition metal element (the sum of manganese and copper) is 1.05:1.00. Heat and stir at 40 degrees to obtain a uniform precursor solution.
[0053] Step S3, weigh 0.04 mmol, 8.4048 g of citric acid monohydrate, transfer it into 25 ml of deionized water, stir it thoroughly to completely dissolve it into a transparent colorless citric acid solution. The mass percentage concentration range of the citric acid solution is 26%.
[0054] Step S4, select a pipette and add the solution of step S2 dropwise into the citric acid solution of step S3, and then continue stirring at 40 ° C until a uniform complex solution is formed.
[0055] Step S5, spray freeze-drying the precursor solution of step S4 to obtain a precursor powder.
[0056] Step S6, placing the precursor powder of step S5 in a crucible, and pre-calcining it in a muffle furnace at 450 °C for 6 h to obtain a pre-calcined powder.
[0057] Step S7, crushing and mixing the sample obtained in step S6 again.
[0058] Step S8, pressing the pre-sintered product obtained in step S7 into thin sheets using a tablet press and a tablet press at a pressure of 15 MPa.
[0059] Step S9, placing the tablet product obtained in step S8 in a corundum porcelain boat, calcining at 800 ° C for 12 h in an air atmosphere in a muffle furnace, and cooling naturally.
[0060] Step S10, after the sample in step S9 is naturally cooled to room temperature, the sample is taken out and re-ground, and the ground final product is transferred to an anhydrous and oxygen-free glove box for storage. The final black powder obtained is Na 1.1 Mn 0.8 Cu 0.2 O2 material.
[0061] This embodiment provides a method for preparing a high-sodium layered oxide material, which can be used to prepare the high-sodium layered oxide material described in the above embodiment 13. The method provided in this embodiment is simple, easy to implement, low-cost, and suitable for large-scale manufacturing applications.
[0062] Example 4 In this embodiment, the sol-gel method described in the above-mentioned embodiment 2 is used to prepare the high-sodium layered oxide material.
[0063] Step S1, preparing Na by sol-gel method 1.00 Mn 0.8 Cu 0.2 O2 material.
[0064] Step S2, the specific process is as follows: weigh 0.021 mmol of sodium nitrate, 0.02 mmol of 50 wt% manganese nitrate tetrahydrate, and copper nitrate trihydrate in proportion, and dissolve them in 50 ml of deionized water, wherein the molar ratio of sodium element to transition metal element (the sum of manganese and copper) is 1.05:1.00. Heat and stir at 40 degrees to obtain a uniform precursor solution.
[0065] Step S3, weigh 0.04 mmol, 8.4048 g of citric acid monohydrate, transfer it into 25 ml of deionized water, stir it thoroughly to completely dissolve it into a transparent colorless citric acid solution. The mass percentage concentration range of the citric acid solution is 26%.
[0066] Step S4, select a pipette and add the solution of step S2 dropwise into the citric acid solution of step S3, and then continue stirring at 80° C. until a uniform wet gel is formed.
[0067] Step S5, placing the wet gel obtained in step S4 in a freeze dryer for freeze drying to obtain a precursor dry gel.
[0068] Step S6, placing the dry gel obtained in step S5 in a mortar and grinding it evenly to obtain a fine powder.
[0069] Step S7, placing the powder from step S6 in a crucible and pre-calcining it in a muffle furnace at 450 °C for 6 h.
[0070] Step S8, pressing the pre-sintered product obtained in step S7 into thin sheets using a tablet press and a tablet press at a pressure of 15 MPa.
[0071] Step S9, placing the tablet product obtained in step S8 in a corundum porcelain boat, calcining at 800 ° C for 12 h in an air atmosphere in a muffle furnace, and cooling naturally. Step S10, after the sample in step S9 is naturally cooled to room temperature, the sample is taken out and re-ground, and the ground final product is transferred to an anhydrous and oxygen-free glove box for storage. The final black powder obtained is Na 1.00 Mn 0.8 Cu 0.2 O2 material.
[0072] Step S11, characterize the electrochemical performance of step S10 by constant current charge and discharge method. The mass ratio of active material, conductive agent (Super P) and binder (PVDF) in the electrode is 75:15:10. The battery is assembled into a 2032 button cell in an anhydrous and oxygen-free glove box using the electrode as the working electrode, sodium as the counter electrode, and 1M NaPF6EC / DEC (vol 1:1) as the electrolyte.
[0073] Step S12, using constant current charge and discharge mode, 3 pre-cycles at 0.1C, 1C current density cycle charge and discharge test, the charge and discharge range is 2.0 - 4.5 V. The results are shown in Figure 2, the capacity at 0.1C in 2.0 - 4.5 V is 100.6mAh g -1 , the highest cycle retention rate at 1C is 280 cycles, 90% (calculated at maximum capacity).
[0074] Comparative Example 1 In this embodiment, the sol-gel method described in the above-mentioned embodiment 2 is used to prepare the high sodium layered oxide material, but with different processes and proportions.
[0075] Step S1, preparing Na by sol-gel method 1.00 Mn 0.8 Cu 0.2 O2 material.
[0076] Step S2, the specific process is as follows: weigh 0.021 mmol of sodium nitrate, 0.02 mmol of 50 wt% manganese nitrate tetrahydrate, and copper nitrate trihydrate in proportion, and dissolve them in 50 ml of deionized water, wherein the molar ratio of sodium element to transition metal element (the sum of manganese and copper) is 1.05:1.00. Heat and stir at 40 degrees to obtain a uniform precursor solution.
[0077] Step S3, weigh 0.04 mmol, 8.4048 g of citric acid monohydrate, transfer it into 25 ml of deionized water, stir it thoroughly to completely dissolve it into a transparent colorless citric acid solution. The mass percentage concentration range of the citric acid solution is 26%.
[0078] Step S4, select a pipette and add the solution of step S2 dropwise into the citric acid solution of step S3, and then continue stirring at 80° C. until a uniform wet gel is formed.
[0079] Step S5, placing the wet gel obtained in step S4 in an oven at 120°C to dry.
[0080] Step S6, placing the dry gel obtained in step S5 in a mortar and grinding it evenly to obtain a fine powder.
[0081] Step S7, placing the powder from step S6 in a crucible and pre-calcining it in a muffle furnace at 450 °C for 6 h.
[0082] Step S8, pressing the pre-sintered product obtained in step S7 into thin sheets using a tablet press and a tablet press at a pressure of 15 MPa.
[0083] Step S9, placing the tablet product obtained in step S8 in a corundum porcelain boat, calcining at 750 ° C for 8 h in an air atmosphere in a muffle furnace, and cooling naturally.
[0084] Step S10, after the sample in step S9 is naturally cooled to room temperature, the sample is taken out and re-ground, and the ground final product is transferred to an anhydrous and oxygen-free glove box for storage. The final black powder obtained is the non-P2 phase Na 1.00 Mn 0.8 Cu 0.2 O2 material.
[0085] The electrochemical properties of the above materials were characterized by constant current charge and discharge method. The mass ratio of active material, conductive agent (Super P) and binder (PVDF) in the electrode was 75:15:10. The battery was assembled into a 2032 button cell in an anhydrous and oxygen-free glove box using the electrode as the working electrode, sodium as the counter electrode, and 1M NaPF6EC / DEC (vol 1:1) as the electrolyte.
[0086] Using the constant current charge and discharge mode, 3 pre-cycles at 0.1C, and 1C current density cycle charge and discharge test, the charge and discharge range is 2.0 - 4.5 V. The results are shown in Figure 2. The capacity at 0.1C in 2.0 - 4.5 V is 100.6 mAh g -1 , the comparison chart is as follows Figure 3 As shown, the circulation effect is obviously not as good as the black powder material Na in Example 2 above. 1.00 Mn 0.8 Cu 0.2 O2.
[0087] Table 1 Performance test results As can be seen from Table 1, Examples 1 to 4 are pure phase high sodium state P2 type materials synthesized by different methods. It can be seen that under the charge and discharge conditions of 1C, they have similar capacities. However, there are slight differences between different methods, among which Examples 2 to 4 have higher capacities of 92.3, 92.3, and 92.2 mAh / g, respectively, showing excellent performance. This is because the materials synthesized by the synthesis methods of Examples 2 to 4 are more uniform. In Comparative Example 1, the 1C first week discharge is only 70.1 mAh / g. This is because the material synthesized in Comparative Example 1 is a non-P2 pure phase material. The cycle retention rate is 45% for 280 cycles, which is significantly lower than the above examples.
[0088] Figure 1 This is the X-ray diffraction pattern of the high-sodium layered oxide material with different sodium contents in Example 2; it can be seen that the synthesized Na content is in the range of 0.98 to 1.3, and the materials all show a pure phase structure of the P2 phase, verifying that the materials synthesized under the protection conditions of this patent are all pure phase P2 type high-sodium materials.
[0089] Figure 2 The optimum ratio of P2 - Na in Example 2 is x Mn 1-y Cu y O 2+δ 300 cycles of 1C long cycle diagram of a series of layered oxide materials; It can be seen from the figure that the material synthesized by Example 2 has good cycle stability. After 300 cycles at 2-4.5V and 1C rate conditions, the cycle retention rate is about 87%.
[0090] Figure 3 The 300-cycle 1C long cycle comparison chart of different oxide materials generated under the conditions of Example 4 and Comparative Example 1. It can be seen that compared with the non-pure phase P2 type material synthesized in Comparative Example 1, the 300-cycle cycle retention rate is 44.29%, and the material in Example 4 has significantly higher capacity and better cycle retention rate, which is 89.64%, indicating the superiority of the synthesis method of this patent.
[0091] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A sodium-ion battery positive electrode high sodium state P2 type layered oxide material, characterized in that: The general chemical formula of the high sodium state P2-type layered oxide material is: Na x Mn 1-y Cu y O 2+δ ; Among them, Cu and Mn form octahedral structures with the six adjacent oxygen atoms respectively, and multiple octahedral structures are arranged with the same edge to form a transition metal layer; sodium ions are located between every two transition metal layers, forming a layered oxide of the P2 phase, and the space group is P63 / mmc; The relationship between x, y and z satisfies the charge balance: x+3(1-y)+2y=2(2+δ), where 0.98<x≤1.4, 0.18≤y≤0.35; -0.05≤δ≤0.
05.
2. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 1, characterized in that: The high sodium state P2 type layered oxide material is prepared by a sol-gel method or a solid phase method.
3. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 2, characterized in that: The preparation process of the sol-gel method includes the following steps: S1. Preparation of precursor solution: Sodium nitrate, manganese nitrate and copper nitrate are weighed according to a molar ratio of sodium element to manganese element of 0.98-1.512, and dissolved in deionized water, and stirred to obtain a uniform precursor solution; S2. Preparation of citric acid solution: weigh citric acid monohydrate, stir to completely dissolve it to obtain a citric acid solution with a mass percentage concentration range of 10% to 30%; S3, preparation of precursor dry gel: adding the precursor solution in step S1 to the citric acid solution in step S2, and then continuously stirring at a controlled temperature of 40-60° C. to form a uniform wet gel, and drying the wet gel to obtain a precursor dry gel; S4, high temperature calcination: pre-calcine the precursor dry gel described in step S3 in an air atmosphere at 450-550°C for 4-8h, crush and mix again, calcine in an air atmosphere at 750-900°C for 8-15h, and obtain a high sodium state P2 type layered oxide positive electrode material after natural cooling.
4. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 3, characterized in that: In the sol-gel method, the molar ratio of metal ions to citric acid monohydrate in the precursor solution is 0.5~1.
5. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 4, characterized in that: In step S3, the drying method is freeze drying and / or spray drying.
6. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 2, characterized in that: The preparation process of the solid phase method includes the following steps: A1. Preparation of precursor powder: Sodium carbonate, manganese source and copper oxide are weighed according to a stoichiometric ratio and mixed to obtain a precursor powder; A2. High-temperature calcination: calcine the precursor powder described in A1 at 750-900 °C in an air atmosphere for 8-15 hours, and then cool naturally to obtain a high-sodium P2-type layered oxide positive electrode material.
7. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 6, characterized in that: In step A1, the molar ratio of sodium element to transition metal element is 0.98-1.
512.
8. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 6, characterized in that: In step A1, the manganese source is one or more of manganese trioxide, manganese dioxide, and manganese carbonate.
9. The sodium ion battery positive electrode high sodium state P2 type layered oxide material according to claim 6, characterized in that: In step A1, the mixing method is ball milling and / or stirring.
Citation Information
Patent Citations
Sodium-rich P2-phase layered oxide material and preparation method and application thereof
CN104795560A
Copper-manganese-based layered oxide material and preparation method thereof, positive electrode and sodium ion battery
CN115911332A
P2-phase positive electrode material, preparation method thereof and sodium battery
CN118335968A